Designing Strategies for Cleft Lip and Palate Care - Ahmad Almasri, Mazen (IntechOpen, 2017)
In Designing Strategies for Cleft Lip and Palate Care it was aimed to link the epidemiology from different areas in the world with the interspecialty surgical care and the future genetic research projects. The objective is to concisely discuss the methodology of interspecialty care and stimulate future ideas for prophylactically managing or preventing such deformities. I am confident that one day the surgical interventions that bombard the patients from the day of newborn delivery and throughout the years of youth should be significantly decreased based on the genetic prophylactic intervention, probably.